Immobilization and stabilization of an endoxylanase from Bacillus subtilis (XynA) for xylooligosaccharides (XOs) production - Milessi, Thais S.S.; Kopp, Willian; Rojas, Mayerlenis J.; Manrich, Anny; Baptista-Neto, Alvaro [UNESP]; Tardioli, Paulo W.; Giordano, Roberto C.; Fernandez-Lafuente, Roberto; Guisan, Jose M.; Giordano, Raquel L.C. (Elsevier, 2016)
Xylooligosaccharides (XOs) are small oligomers constituted by 2-10 units of xylan monomers, with important nutraceutical properties. They can be produced through hydrolysis of xylan catalyzed by an endoxylanase. The use of immobilized and stabilized enzymes may decrease the industrial process costs. In this study, XynA, a recombinant enzyme from B. subtilis, was immobilized in three different supports: agarose and chitosan activated with glyoxal groups and chitosan activated with glutaraldehyde. High immobilization yields were obtained, 100% for agarose-glyoxal and chitosan-glutaraldehyde, 82% for chitosan-glyoxal, with recovered activities of 42.7 (±1.3), 10.7 ± 0.8 and 53.6% (± 1.7), respectively. A great increase in the thermal stability of the enzyme (at 56 °C, pH 5.5) was achieved for the glyoxal derivatives: 75-fold for chitosan and 8600-fold for agarose. The great thermal stability obtained to the derivative agarose-glyoxal can be explained by the enzyme immobilization through lysine residues located in unstable sites of the protein structure. The agarose-glyoxal derivative was tested in the production of XOs (X2, X3 and X4) from soluble and conventional birchwood xylan, reaching approximately 20% of conversion in 3 h and 23% in 24 h, without the undesirable xylose production. After 10 cycles of hydrolysis, the conversion remained almost unchanged.
Keywords: B. subtilisendoxylanase; Immobilization; Stabilization; Xylooligosaccharides; XynA